If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4u + -2 = 5u Reorder the terms: -2 + 4u = 5u Solving -2 + 4u = 5u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-5u' to each side of the equation. -2 + 4u + -5u = 5u + -5u Combine like terms: 4u + -5u = -1u -2 + -1u = 5u + -5u Combine like terms: 5u + -5u = 0 -2 + -1u = 0 Add '2' to each side of the equation. -2 + 2 + -1u = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1u = 0 + 2 -1u = 0 + 2 Combine like terms: 0 + 2 = 2 -1u = 2 Divide each side by '-1'. u = -2 Simplifying u = -2
| -3q=7+4q | | 2x*2=4 | | 8u=7u-6 | | 49x-50+2=x+3 | | -7y+5y=-10+16 | | 5x(2x-9)-8(2x-9)= | | 4(3x-3)=4x-4 | | 5v+1=4v-3 | | 7w=.875 | | 11-2(3p-10)=5(4-p) | | 3=-2u | | .4285714286y=-2 | | 4000=700x+500 | | 6-2=-9v+v | | 3(2n+5)=3 | | x^3-12=0 | | 20-8=-3z+9z | | 3000=400x+200 | | -9-7(8-3n)=33+7n | | 7x-x=-1-3 | | 2(5x-16)=18 | | b+1=-3-(-2) | | 2000=600x+200 | | 10(2x+1)=70 | | 1000=400*x+200 | | 4x^2-10x=0 | | 2(5x-6)=4 | | 4x^2-19x+53=9x+8 | | 9+8x=3(-10+7x) | | 9(2x+3)=81 | | x^2-11x-38=-3x-5 | | 2(4x+2)=3 |